Peningkatan Produktivitas dan Profitabilitas Petani Pisang Barlin di Desa Papringan Kecamatan Temayang Kabupaten Bojonegoro - Putra, Arda Purnama; Pratiwi, Iqlima; Prajogo, Uke (Jurnal ABM Mengabdi, 2024)
Barlin Banana is a leading agricultural products in Bojonegoro. However, the shelflife of Pisang Barlin only 10 days at room temperature. Therefore, a lot of which iswasted because of rotten bananas. As a result, the loss is very large bananagrowers. The selling price of the product is also relatively cheap only around Rp1500 per comb. These conditions led to the welfare of farmers Barlin Banana stilllow. Farmers group Barlin Banana "Papringan" which became a partner in thePKM program is in District Papringan Bojonegoro. Farmers group Barlin Banana"Papringan" was established in 2005 with the purpose as a means of fostering theBarlin Banana Farmers so that productivity and quality of crops Barlin Bananacan be maximized. Existence of banana growers group "Papringan" is felt by thesurrounding community. Since its founding five years ago, members of this groupof banana farmers has reached 100 farmers. If we assume that each farmer groupmembers bear live an average of 3 persons consisting of a wife and 2 children, thenit implies the existence of a group of banana farmers "Papringan" relates to thefate of 400 people in the District Papringan Bojonegoro. Activities undertaken inthe stages: 1) the selection of the group's strategic objectives, 2) grant reliefmachinery and equipment which include machine vacuum fryer, spinner, sealer,tool kit, and digital scales, 3) test, 4) ttraining of machine operation , 4) monitoringand evaluation.The results of this activity is a group of farmers Barlin Banana partners have ownedmachinery and processing equipment Barlin Banana and can operate it well. Anincrease product shelf life of up to 7 months, the farmers profit increased 600%from Rp 1,000 to Rp. 6000. So that the welfare of farmers has also increased